2010
DOI: 10.3109/13668250903501499
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a stress-relief initiative for primary caregivers of adolescents with intellectual disability

Abstract: The study highlights that a "face-to-face" workshop is an effective way to decrease levels of depressive stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Caregivers' depression was based on CES‐D scores rather than diagnosis by a psychiatrist, thus precluding a precise estimation of depression risk using the Finding a Balance Scale cutoff score. However, our data indicated that 33% of our caregiver participants were at high risk for depressive status, which is well within the range of the prevalence of depressive symptoms among family caregivers throughout Taiwan, that is, 22.1–45% (Hu et al, ; Song & Singer, ; Tsai & Tsai, ). Finally, our study used a cross‐sectional design, limiting understanding of causal relationships between success at finding a balance point and outcomes such as lower risk for depression and better health‐related quality of life.…”
Section: Discussionsupporting
confidence: 57%
“…Caregivers' depression was based on CES‐D scores rather than diagnosis by a psychiatrist, thus precluding a precise estimation of depression risk using the Finding a Balance Scale cutoff score. However, our data indicated that 33% of our caregiver participants were at high risk for depressive status, which is well within the range of the prevalence of depressive symptoms among family caregivers throughout Taiwan, that is, 22.1–45% (Hu et al, ; Song & Singer, ; Tsai & Tsai, ). Finally, our study used a cross‐sectional design, limiting understanding of causal relationships between success at finding a balance point and outcomes such as lower risk for depression and better health‐related quality of life.…”
Section: Discussionsupporting
confidence: 57%
“…3 & 4 ) and only a small number of parents (4.7% of the fathers and 4.9% of the mothers) had a normal score on HADS for depression. This agreed with Tomkiewicz and Marcia findings 9,10 . Furthermore, the study showed no significant association between the social and psychological impacts and the number and age of the mentally retarded children or the degree of severity of MR (Tables 1-6).…”
Section: Discussionsupporting
confidence: 93%
“…Interventions that support and promote caregivers’ emotional well‐being may reduce QoL losses among the children. A study on effectiveness of a stress‐relief initiative for primary caregivers of adolescents with ID showed that a stress management workshop is an effective way to decrease levels of parental stress (Hu et al. 2010).…”
Section: Discussionmentioning
confidence: 99%